(untitled) - Manahan, Stanley E. (Boca Raton, 1994)
The classic text in the field, Environmental Chemistry, offers a basic understanding of environmental chemistry and its applications. This new, thoroughly revised and updated Sixth Edition has been rigorously reviewed by experts in the field. It is essential for anyone entering the chemical profession, as well as those actively engaged in it. Even non-chemists, including engineers, regulators, and lawyers, will find much of the information accessible with a review of the chapters on general and organic chemistry.
Phân tích và đánh giá hóa lý nước
Keywords: Environmental chemistry